Numerical investigation of the flow around a feather shuttlecock with rotation - Hart, J.; Potts, J. (Proceedings, 2020)
This paper presents the first scale resolving computational fluid dynamic (CFD) investigation of a geometrically realistic feather shuttlecock with rotation at a high Reynolds number. Rotation was found to reduce the drag coefficient of the shuttlecock. However, the drag coefficient is shown to be independent of the Reynolds number for both rotating and statically fixed shuttlecocks. Particular attention is given to the influence of rotation on the development of flow structures. Rotation is shown to have a clear influence on the formation of flow structures particularly from the feather vanes, and aft of the shuttlecock base. This further raises concerns regarding wind tunnel studies that use traditional experimental sting mounts; typically inserted into this aft region, they have potential to compromise both flow structure and resultant drag forces. As CFD does not necessitate use of a sting with proper application, it has great potential for a detailed study and analysis of shuttlecocks.